Parameter-Optimization-Based Adaptive Fault-Tolerant Control for a Quadrotor UAV Using Fuzzy Disturbance Observers - Ren, Yong; Sun, Yaobin; Liu, Zhijie; Lam, Hak-Keung (IEEE transactions on fuzzy systems, 2025)
This article investigates an adaptive fault-tolerant control (AFTC) problem for a quadrotor UAV subject to external disturbances, actuator faults and saturations, and system uncertainties. First, to ensure accurate estimation of external disturbances, the novel second-order fuzzy disturbance observers (SOFDOs) are proposed by combining fuzzy logic systems and projection functions. Unlike existing research, the proposed SOFDOs effectively solve the coupled problem between parameter estimations caused by actuator faults and disturbance estimations. Then, the AFTC scheme is designed based on the Lyapunov direct method to guarantee the stability of the closed-loop system for the quadrotor UAV. In addition, since the chosen control parameters are selected based on stability concerns without considering performance optimization, a modified particle swarm optimization algorithm is introduced to optimize the design parameters of the proposed scheme. At last, the effectiveness of the proposed parameter-optimization-based AFTC scheme is verified through numerical simulations.